Caminhos de sobrevivência institucional: a gestão do Núcleo de Oficinas e Artes Profissionalizantes Laís Aderne - Noronha, Helen Lopes (2010)
The object of this study is the organizational management, particularly the relational processenvironment organization focused on the survival of the space Department of the Arts and Crafts Mestre Raimundo Cardoso linked to the structural arrangement of the Liceu do Paracuri.. Aimed to understand the ways of organizational survival, from the actors' perception of the Center for Arts Career Workshops and Lais Aderne, with investments that discuss the theoretical models of management, institutional theory, cultural organization and institutionalization of public education requirement of the municipal light LDB. (1996) used a qualitative approach with a view to RICHARDSON (1985). The data generated were analyzed based on the technique of content analysis, the thematic type [categorical] Bardin (1977). The results indicate that the institutionalization of the arrangement of the Liceu do Paracuri emerges meet the legal requirement of the autonomy of municipal educational administration under the aegis of sustainable development, quality of life and basic education from the municipal Hélio Gueiros (1993-1996 ). More specifically the Center for Arts and Crafts Laís Aderne, the unit of analysis, the subjects said that this space is designed as a link between the demands of school and community searching through interdisciplinary activities educate and train manpower mainly potter. They did mention the existence of institutional factors (history, culture, habits, values) represent a strong socio-cultural element to the actors belonging to the core that guides behavior and actions of these individuals, fueled by a sense of hope, inclusion of future artisans in culture ceramist. It made a shared management, the existence of a unique work through cultural revival. However, over the course of time, the core is faced with dilemmas of managing transitions mainly regarding governmental, technological beyond endurance by the craftsmen for the optimization of their work. The conclusion - that the paths chosen for the organizational survival of the core meaning and guiding their actions in the systematization of conduct, representations, memories and traditions through habits and choices of consensus, the viewpoint of the actors